Primary and secondary clarithromycin resistance in Helicobacter pylori and mathematical modeling of the role of macrolides - Éva Kocsmár (Nature Portfolio, 2021)
Clarithromycin is a macrolide antibiotic widely used for eradication of Helicobacter pylori infection. Here, Kocsmár et al. study clarithromycin resistance and previous macrolide consumption in 4,744 H. pylori-infected patients, shedding light into the sources of primary resistant cases and the role played by prior consumption of macrolides for non-eradication purposes.